A pilot randomized controlled trial comparing the outcome of sustained low efficiency daily dialysis (sledd) with sustained low efficiency daily diafiltration (sledd-f) in critical care patients with acute kidney injury - Ab Wahab, Mohd Nor Azri (2015)

(untitled)
Background: Acute Kidney Injury (AKI) is common in Critical Care patient and cause significant increase mortality and morbidity. Early management of Renal Replacement Therapy with correct dose and suitable modality is an essential intervention in severe AKI. Hybrid therapy like Sustained Low Efficiency Daily Dialysis (SLEDD) has emerged as an alternative to CRRT in Intensive Care Unit (ICU) patients. Sustained Low Efficiency Daily Diafiltration (SLEDD-f), which contains both diffusion and convection principles, also suggested to provides stable renal replacement therapy. Thus, we formulated this study to compare the outcome between the administration of SLEDD and SLEDD-f in Critical Care patient with Acute Kidney Injury. Objectives: The objective of this randomized control trial is to compare the Intensive Care Unit (ICU) Survival between SLEDD and SLEDD-f in Critical Care patient with Acute Kidney Injury. The specific objective is to compare Length of Stay in ICU and Hospital, Days of Ventilatory support, as well as control of acid base balance, small solute (urea and creatinine) and electrolytes (sodium and potassium) between SLEDD and SLEDD-f. Methods: Fourteen patient, with Acute Kidney Injury in Critical Care were selected with selection criteria were randomized into two group to received either Sustained Low Efficiency Daily Dialysis (SLEDD) or Sustained Low Efficiency Daily Diafiltration (SLEDD-f) for Renal Replacement Therapy. Selected parameters and blood investigation were recorded and compared including ICU predicted score, acid base status, renal function test, urine output and electrolytes are all taken during admission to hospital and critical care, before initiating the dialysis, day one after starting the dialysis until discharged from critical care and hospital, as well as during follow up until 42 days after dialysis. 3 month mortality also been recorded. Results: In both SLEDD and SLEDD-f group, the distributions of social-demographic, medical background status, as well as ICU predicted mortality like SOFA, SAPS II and APACHE II were similar. 85.7% of the AKI was due to sepsis while 14.3% due to multifactorial cause. Overall, there is no significant differences of outcome distribution (ICU and hospital survival, length of ICU and hospital stay; and duration of ventilatory support) and parameter distribution (urea, creatinine, sodium, pottasium and acid base balance) between patients receiving SLEDD and SLEDD-f technique (p>0.05). Mortality rate at day 60 reveals no significant difference in between both modalities with SLEDD having 42.9% mortality and SLEDD-f 14.3 % (p=0.554). In general, patients in SLEDD-f group have a shorter duration of ICU stay (median, 11 days [IQR 5 to 37 days]), duration of ventilation (median, 5 days [IQR 4 to 33 days]) and have a higher ICU survival (85.7%) compare to SLEDD group, but this was not statistically significant. Meanwhile, SLEDD have a shorter duration of hospital stay (median, 25 days [IQR 16 to 29 days]) and this may result from higher mortality compare to SLEDD-f as the survivor may have prolonged length of stay at hospital. Conclusion: The administrations of SLEDD and SLEDD-f in ICU patients with AKI are feasible and comparable in terms of ICU survival, Length of ICU stay, Days of Ventilatory support as well as control of small solutes, electrolytes and acid base balance. Therefore, SLEDD-f can be used as an alternative therapy other than the conventional SLEDD with shorter duration of 4 hours as compared to SLEDD of 6 hours.